The Efficacy of a Three-Week Low-Calorie Diet in Decreasing Liver Volume Pre-Laparoscopic Sleeve Surgery: A Randomized Clinical Trial: Efektivitas Diet Rendah Kalori Selama Tiga Minggu dalam Mengurangi Volume Hati Pra-Bedah Lengan Laparoskopi: Uji Klinis Secara Acak - Sura Aqeel Sadiq; Sajjad Salim Issa; Jasim D. Saud (Universitas Muhammadiyah Sidoarjo, 2024)
Background: For obese individuals having significant non-bariatric surgery, better preoperative weight loss techniques are required. Objectives: To identify the efficacy of a three-week low-calorie diet in decreasing liver volume pre-laparoscopic sleeve surgery. Methods: Twenty-five morbidly obese individuals who were scheduled for LSG participated in this interventional trial. Every patient was instructed to adhere to a low-calorie, restrictive diet for three weeks, and their liver span was measured by ultrasonography before and after the regimen. The end measurements were the effects of the preoperative diet on liver span and liver enzymes (ALT and AST). Results: Liver span is significantly reduced as a function of diet. Weight and body mass index showed a favorable correlation with changes in liver size. Liver enzyme levels significantly increased. Conclusion: A low-calorie diet successfully decreased liver size for three weeks before bariatric surgery. Highlights: Evaluate 3-week low-calorie diet's effect on liver size before surgery. 25 obese patients followed low-calorie diet; liver span measured pre/post. Diet reduced liver size, correlated with weight, but increased liver enzymes. Keywords: Sleeve Surgery, Liver Volume, Three weeks, Efficacy